Garfield (2012), volume 2 ebook - Davis, Jim (Garfield (2012), 2015)
Garfield's return to comics continues! Writer Mark Evanier (GARFIELD AND FRIENDS) and longtime GARFIELD strip artist Gary Barker introduce Garfield and the gang to many new friends, including a mouse that wants to be a cat (and sometimes a dog), a mummy, and Pet Force! Yes, we're going to Planet Dorkon to hang out with the galaxy's greatest superheroes. Get ready more a whole new round of fun for the entire family!